2017
DOI: 10.1136/sextrans-2016-052969
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing experiences and their implications for patient engagement with HIV care and treatment on the eve of ‘test and treat’: findings from a multicountry qualitative study

Abstract: ObjectiveIn view of expanding ‘test and treat’ initiatives, we sought to elicit how the experience of HIV testing influenced subsequent engagement in HIV care among people diagnosed with HIV.MethodsAs part of a multisite qualitative study, we conducted in-depth interviews in Uganda, South Africa, Tanzania, Kenya, Malawi and Zimbabwe with 5–10 health workers and 28–59 people living with HIV, per country. Topic guides covered patient and provider experiences of HIV testing and treatment services. Themes were der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…14,[37][38][39][40][41] Retesting can be motivated by multiple factors, one of them being the ability to confirm the accuracy of the initial test result. [41][42][43] Another data. Given the cross-sectional nature of these metrics, they could be more sensitive to the elicited model's prior distributions in early years.…”
Section: Resultsmentioning
confidence: 99%
“…14,[37][38][39][40][41] Retesting can be motivated by multiple factors, one of them being the ability to confirm the accuracy of the initial test result. [41][42][43] Another data. Given the cross-sectional nature of these metrics, they could be more sensitive to the elicited model's prior distributions in early years.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting prior reports that many PLHIV retest for HIV after diagnosis, BCPE staff used a standard form to identify 1,407 testers who had been previously diagnosed, of whom 819 were currently in HIV care [72, 73]. Thus, routine assessment of prior diagnostic and HIV-care status of all clients who test HIV-positive is critical, and may be particularly important as countries approach diagnostic coverage among PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…We did not identify retesting to be specifically related to pregnancy, as less than 11% of women who retested were pregnant. Other studies show that repeat testing for those already diagnosed with HIV has been identified as an issue as some patients question the accuracy of test results (Wringe et al, 2017), or simply wish additional verification. It is important to understand why retesting is occurring, as approximately 8% of cases retesting had already started care at the first facility before being retested at a different facility, which can occur if a patient transfers to another facility without disclosing it to either facility.…”
Section: Discussionmentioning
confidence: 99%